Comprehensive Mechanistic Modelling of Non-isothermal CO2 Adsorption in Fixed Packed Bed - Federico Zedda; Mariano Casu; Federico Atzori; Roberto Orrù; Giacomo Cao; Alessandro Concas (Chemical Engineering Transactions, 2024)
A model based on conservation laws was developed to simulate the continuous, non-isothermal CO2 adsorption on porous materials in a packed bed. A set of parameters inferred from correlations between dimensionless numbers was used to mathematically solve the problem. The developed rigorous model includes a set of partial differential equations with proper boundary conditions. By adapting the equations for numerical solutions, it describes the process under unsteady state conditions, enabling the derivation of temperature and concentration profiles essential for process analysis. Finally, a sensitivity analysis was carried out to assess the effect of parameters on the model's solution.